Mechanism of sodium nitroprusside regulating ginseng quality - Wei Zhang; Pengcheng Yu; Wenfei Liu; Liyang Wang; Xiaowen Song; Yao Yao; Xiubo Liu; Xiangcai Meng (Scientific Reports)
Abstract The roots of Panax ginseng C. A. Meyer (ginseng) are one of the traditional medicinal herbs in Asian countries and is known as the “king of all herbs”. The most important active components of ginseng are the secondary metabolite saponins, which are closely related to ecological stress. Unsuitable ecological stress can generate a large amount of reactive oxygen species (ROS), by which the secondary metabolism is regulated, and the quality of herbs can be significantly improved. The purpose of this study was to investigate the effect of sodium nitroprusside (SNP) treatment on the quality of fresh ginseng roots. In this study, 5-year-old fresh ginseng was exposed to 0.1, 0.5, and 2 mmol/L SNP, a nitric oxide (NO) donor for five consecutive days. SNP significantly increased the levels of O2 ·−, H2O2, malondialdehyde (MDA), NADPH oxidase (NOX), superoxide dismutase (SOD), catalase (CAT), peroxides (POD), ascorbate peroxidase (APX), glutathione reductase (GR), ascorbate (AsA) and GSH/GSSG. The main root treated by 0.5 mmol/L SNP for three days was the best, with the activities of the key enzymes of the ginsenoside synthesis pathway, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR), farnesyl pyrophosphate synthase (FPS), squalene synthase (SS), squalene epoxidase (SE), and dammarane diol-II synthase (DS) activities increased markedly; the ginsenosides Rg1 + Re, Rb1, Rf, Rc, Rg2 + Rh1 and the total ginsenoside contents increased by 51.0%, 77.7%, 44.6%, 26.8%, 63.2% and 48.2%, respectively, but only a trace amount of the ginsenoside monomer Rb2 decreased 23.4%. The fibrous roots treated by 0.1 mmol/L SNP for four days showed the best effect, HMGCR, FPS, SS, SE, and DS also increased significantly; ginsenosides Rg1 + Re, Rb1, Ro, Rc, Rf, Rb3, Rb2, and total saponin contents increased 37.6%, 47.8%, 34.2%, 75.1%, 51.0%, 49.4%, 28.3%, and 20.4%, respectively. The 1,3-diphosphoglycerate (1,3-DPG) and phosphoenolpyruvate carboxylase (PEPC), related to primary metabolism, were also significantly elevated. The Morris water maze (MWM), histopathological analysis and oxidative stress indexes in brain tissues were used to evaluate the anti-aging effect, indicating that the SNP-treated ginseng further ameliorated D-gal-induced the impaired memory function and oxidative stress in mice, implying the efficacy of SNP-treated ginseng was better than untreated ginseng’s. SNP can build the physiological state of ginseng under ecological stress, stimulate the antioxidant protection mechanism, increase the secondary metabolites, and improve the quality of ginseng.